Effect of YangxueJiedu Decoction on the expression levels of IL-36 in psoriasis-like lesions in mice - Qi ZHANG; Lei ZHU; Yuqi HUANG; Yongfeng CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To explore the effect of YangxueJiedu decoction on IL-36 expression in a mouse model of imiquimod-induced psoriasis-like lesions. Methods: Eighteen mice were randomly divided into the control, model and experimental groups, with 6 mice per group. The psoriasis severity was assessed by PASI score. The expression levels of mRNA for IL-36α, IL-36β, IL-36γ, and IL-36Ra were measured by RT-qPCR. Expression levels of IL-36β protein were evaluated by both Western blot and immunohistochemistry. Results: PASI scores were significantly lower in experimental group than in the model group (1.17±0.37 vs 7.83±0.69, t=19.07, P<0.05). Likewise, the expression levels of IL-36β mRNA were also significantly lower in the experimental group than in the model group (1.85±0.28 vs 4.85±0.42, t=8.01, P<0.01). However, expression levels of IL-36α, IL-36γ and IL-36Ra mRNA were comparable between the experimental group and the model group. In the model group, IL-36β was mainly expressed in the nucleus and cytoplasm of the granular layer and the middle and upper spinous layers, with little expression in the dermis. In the experimental group, the dermis expressed little IL-36β, while the epidermis expressed very little or was absence of IL-36β. Consistent with immunohistochemistry, expression levels of IL-36β were significantly lower in the experimental group than in the model group (2.50±0.24 vs 3.27±0.32, t=3.31, P<0.05). Conclusion: YangxueJiedu decoction can decrease PASI scores by down-regulation of IL-36β expression in imiquimod-induced psoriasis-like lesions.